Outdoor Pet Tracking and Health Monitoring System - Mohd Zahari, Aini Syafinas; Baharuddin, Elfarizanis (Evolution in Electrical and Electronic Engineering, 2023)
This study focused on pet tracking and health monitoring systems using Blynk cloud technologies. Today, Internet of Things (IoT) applications are prevalent. However, the chances of finding out about pets are low. This work aims to develop a tracking and health monitoring system incorporating Internet of Things (IoT) technology. Furthermore, this framework uses the Blynk application to connect to the system for data exchange and the global positioning system (GPS) to monitor the precision of the location. The suggested approach can determine the system’s operability under various weather circumstances. According to the proposed method, the mean accuracy is 79.08% respectively. This project’s objective of developing an outside pet tracking and health monitoring system and determining its functionality has been achieved. In the future, the researchers may utilize a precise temperature sensor and monitoring capabilities for pet health components such as heart rate and recognition behavior.